Qualities Affecting Player Experience of Procedural and Semi-Procedural Character Animations - NORI DAVID JOHANNES SAMUEL (The Graduate School, Ajou University, 2024)
Procedural animations can allow a game to utilize its real-time and nonlinear_x000D_ elements in a different way making animations feel responsive and_x000D_ appealing. This study was conducted in order to show which qualities semi-_x000D_ and fully procedural animation methods can add to the responsiveness and_x000D_ appeal of an endless runner game. It used freely available projects (Rosen,_x000D_ 2019/2023) and methods to create game animations that were found both_x000D_ responsive and appealing to players. The sample size of the study was 24_x000D_ participants (mean age: 26) where over half of the participants were either_x000D_ Vietnamese or Korean, while the remaining were mainly from Asia, apart_x000D_ from two of the participants. A combination of descriptive statistics, two-way_x000D_ AnoVAs and correlation tests were used to analyze self ratings of_x000D_ enjoyment, performance, control, responsiveness, appeal, quality, and_x000D_ character design. In order to contribute with qualitative findings to previous_x000D_ research (Normoyle & Jörg, 2018) that inspired the study, initial coding for_x000D_ thematic analysis was used to find common themes and specific qualities_x000D_ affecting the different measures focusing on responsiveness and appeal._x000D_ Based on its results this study articulates rough guidelines for creators to_x000D_ discover what qualities to focus on when developing procedural animation_x000D_ systems. The semi- and fully procedural animation techniques bring benefits_x000D_ to both responsiveness and appeal, where the fully procedural animation_x000D_ system used requires programming experience but provides smooth results,_x000D_ while the semi- procedural animation technique provides creative freedom_x000D_ for animators not well-versed in programming. This study demonstrates how_x000D_ different qualities affect responsiveness and appeal of a stylized primate_x000D_ character through participants’ ratings and opinions about the character in a_x000D_ simple endless runner game. In the fully procedural version, comments on_x000D_ qualities like character transition delays upon landing/ jumping and moving_x000D_ straight through branches instead of following the curve of these, all_x000D_ negatively affected responsiveness, while appeal was affected positively by how the motion was said to breathe life into an otherwise unappealing and_x000D_ robot-like character design. Semi-procedural versions negatively affected_x000D_ responsiveness because of qualities that complicate landing prediction as_x000D_ well as the character’s obscured eyes, which also detracted from the appeal_x000D_ of the character. Movements that were considered less ape-like also_x000D_ impacted appeal negatively such as the jump while the more ape-like_x000D_ movements such as the swing and slide animations had a positive effect on_x000D_ it. Overall, qualities affecting responsiveness negatively were the character’s_x000D_ speed, clunky turning mechanics, lack of control for the jump and swing_x000D_ were subject to grief in all versions, while the double jump feature had a_x000D_ positive effect. The implications of the study are simpler avenues for rapid_x000D_ prototyping of semi-procedural animations that bring satisfactory results_x000D_ within a short time-frame for a game development project.
학위논문(석사)--미디어학과,2024. 2
Keywords: animation appeal; character animation; procedural animation; responsiveness; semi-procedural animation